Nearshore microbial communities of the Pacific Northwest coasts of Canada and the U.S. - Rhodes, Linda D.; Adams, Nicolaus G.; Gallego Simon, Ramon; Kavanaugh, Maria T.; Alin, Simone R.; Feely, Richard A. (Frontiers in Marine Science, 2024)
A survey of marine pelagic coastal microbial communities was conducted over a large geographic latitude range, from Cape Mendocino in northern California USA to Queen Charlotte Sound in British Columbia Canada, during the spring to summer transition. DNA metabarcoding and flow cytometry were used to characterize microbial communities. Physical and chemical oceanography indicated moderate conditions during the survey with no widespread upwelling, marine heat wave, or other extreme conditions. However, four locations displayed features approaching acidified conditions: Heceta Head, Newport, Copalis Beach, and Cape Flattery. Although bacterial and archaeal communities at the Juan de Fuca canyon and northward had high similarity, those south of the Juan de Fuca canyon were well differentiated from each other. In contrast, eukaryotic microbial communities exhibited stronger geographic differentiation than bacterial and archaeal communities across the extent of the survey. Seawater parameters that were best predictors of bacterial and archaeal community structure were temperature, pH, and dissolved inorganic nutrients (nitrate, phosphate, silicate), while those that were best predictors of eukaryotic microbial community structure were salinity, dissolved oxygen, total alkalinity, and dissolved inorganic nutrients (nitrite, silicate). Although five bacterial and archaeal indicators for potentially corrosive waters were identified (Colwellia, Nitrosopumilus, Nitrosopelagicus, Sup05 cluster, Sva0996 marine group), no eukaryotic microbial indicators were found. Potentially pathogenic taxa detected in the survey included four disease-causing bacteria for mammals, finfish, and/or shellfish (Coxiella, Flavobacterium, Francisella, Tenacibaculum), sixteen genera of microalgae capable of producing biotoxins, and fifteen parasitic species. This study demonstrates the value of coordinating microbial sampling and analysis with broad-scale oceanographic surveys to generate insights into community structures of these important pelagic trophic levels.